Study on the Permeability Evolution and Its Formation Mechanism of Xiaojihan Aquifer Coal Seam under Plastic Flow. (15th February 2020) - Guo, Jingna; Liu, Jiangfeng; Li, Qiang; Chen, Zhanqing
Abstract : Study on permeability evolution of an aquifer coal seam in Western China is of great significance for preventing water inrush disaster and realizing water-conserving coal mining. The permeability evolution of an aquifer coal seam is related to a loading path closely under plastic flow. In this work, permeability variations of the Xiaojihan water-bearing coal seam and Longde nonwater coal seam are researched using a transient method under plastic flow. The experiment results indicated the following: (1) Under the same axial strain, the permeability, relative residual strain, and confining pressure influence coefficient of Xiaojihan coal specimens all decrease in plastic flow with the increase of loading-unloading times and confining pressure, while the permeability recovery coefficient increases during this process. (2) The permeability of Xiaojihan water-bearing coal specimens decreases with the growth of axial strain in plastic flow, resulting in the increase of relative residual strain and reinforcement of plasticity. Besides, the confining pressure influence coefficient decreases and the permeability recovery coefficient decreases slightly with the axial strain. (3) Finally, the permeability of Xiaojihan coal specimens is greater than that of Longde coal specimens, while the confining pressure influence coefficient and permeability recovery coefficient of Longde coal specimens are greater than those of Xiaojihan coal specimens. The closure rate of internal cracks of the water-bearing coal specimen is lower than that of the nonwater coal specimen, which is beneficial for water storage and transport.